An Analysis of Indonesian Language Proficiency in Academic Assignments: A Case Study of Pharmacy Students - Ni Putu Veny Narlianti (Denpasar Institute, 2024)
Indonesian language, as the official and unifying language of Indonesia, plays a critical role in various aspects of life, including education. In higher education, Indonesian serves as a vital medium for effective communication, particularly in expressing scientific ideas. This study aims to explore how pharmacy students utilize the Indonesian language to complete academic assignments. Employing a qualitative descriptive approach, the research seeks to examine the phenomenon of language use in these academic tasks. A purposive sampling method was used to select the research sample, consisting of documents submitted as assignments by pharmacy students. Data were collected through document analysis, focusing on sentence structure, grammar, spelling, and terminology usage. Thematic analysis was employed to analyze the data. The findings provide a detailed account of the language use in pharmacy students' assignments, revealing several recurring linguistic errors. Common issues include errors in word formation, letter usage, word choice, punctuation, sentence construction, and paragraph organization. These challenges are attributed to a limited understanding of linguistic rules and the prevalence of informal writing habits.